2016
DOI: 10.1177/230949901602400128
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondromatosis and Osteochondroma Involving Bilateral Patella and Patellar Tendon: A Case Report

Abstract: We present a 22-year-old man with osteochondromatosis and osteochondroma involving bilateral patella and patellar tendon with restriction of joint movement and severe arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Studies show that OC is associated with good prognosis and low risk of metastasis, but due to the disturbance in the anatomical alignment of the knee joint, the masses are removed by radical resection and the patellar ligament is fixed and stabilized at the connection to the tibial tuberosity (5). In the report of Pandian et al (2016), in a 22-year-old man, bilateral OC masses in the patella and patellar ligament caused severe arthritis, chronic pain, edema, and impaired flexion-extension knee movements (8). In 15% of cases, the mass is surrounded by a calcified cartilage cap around the bony lacuna, and its thickness even reaches >15 mm (4).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that OC is associated with good prognosis and low risk of metastasis, but due to the disturbance in the anatomical alignment of the knee joint, the masses are removed by radical resection and the patellar ligament is fixed and stabilized at the connection to the tibial tuberosity (5). In the report of Pandian et al (2016), in a 22-year-old man, bilateral OC masses in the patella and patellar ligament caused severe arthritis, chronic pain, edema, and impaired flexion-extension knee movements (8). In 15% of cases, the mass is surrounded by a calcified cartilage cap around the bony lacuna, and its thickness even reaches >15 mm (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the disturbance in the anatomical alignment of the knee joint, masses are typically removed by radical resection, and the patellar ligament is fixed and stabilized at the connection to the tibial tuberosity 5 . Pandian et al (2016) reported a case in which a 22‐year‐old man had bilateral OC masses in the patella and patellar ligament, causing severe arthritis, chronic pain, edema, and impaired flexion‐extension knee movements 8 . In 15% of cases, the mass is surrounded by a calcified cartilage cap around the bony lacuna, and its thickness may even exceed 15 mm.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Pandian et al (2016) reported a case in which a 22‐year‐old man had bilateral OC masses in the patella and patellar ligament, causing severe arthritis, chronic pain, edema, and impaired flexion‐extension knee movements. 8 In 15% of cases, the mass is surrounded by a calcified cartilage cap around the bony lacuna, and its thickness may even exceed 15 mm. Tumor lesions are also surrounded by 1–10 cm of cartilaginous cap, which, in the deeper parts, contains trabeculae of spongy bone tissue and osteocyte lacunae secreting bone calcification matrix.…”
Section: Discussionmentioning
confidence: 99%